Effect of alpha1-adrenergic antagonist prazosin on behavioral alterations induced by MK-801 in a spatial memory task in Long-Evans rats - Stuchlík, Aleš; Petrásek, Tomáš; Valeš, Karel (Physiological research, 2009)
Animal models of neuropsychiatric disorders are current topics in behavioral neuroscience. Application of non-competitive antagonists of NMDA receptors (such as MK-801) was proposed as a model of schizophrenia, as it leads to specific behavioral alterations, which are partly analogous to human psychotic symptoms. This study examined an animal model of schizophrenia induced by a systemic application of MK-801 (0.15 and 0.20 mg/kg) into rats tested in the active allothetic place avoidance (AAPA) task. Previous studies suggested that MK-801 may interact in vivo with other neurotransmitter systems, including noradrenergic system. Our experiments therefore evaluated the hypothesis that both locomotor stimulation and deficit in avoidance behavior in AAPA task induced by this drug would be reversible by application of alpha1-adrenergic antagonist prazosin (1 and 2 mg/kg). The results showed that both doses of prazosin partially reversed hyperlocomotion induced by higher doses of MK-801 and an avoidance deficit measured as number of entrances into the shock sector. Interestingly, no effect of prazosin on the MK-801-induced decrease of maximum time between two entrances (another measure of cognitive performance) was observed. These results support previous data showing that prazosin can compensate for the hyperlocomotion induced by MK-801 and newly show that this partial reduction sustains even in the forced locomotor conditions, which are involved in the AAPA task. The study also shows that certain parameters of avoidance efficiency may be closely related to locomotor activity, whereas other measures of cognition may more selectively reflect cognitive changes.
Keywords: alfa blokátory; lokomoce; paměť; prazosin; prostorové chování; schizofrenie; financování organizované; krysa rodu Rattus; Financing, Organized; Avoidance Learning; zvířata; schizofrenie (psychologie); Schizophrenia; Dizocilpine Maleate; Schizophrenic Psychology; Adrenergic alpha-Antagonists; Excitatory Amino Acid Antagonists; Rats, Long-Evans; Prazosin; učení vyhýbat se; Male; antagonisté excitačních aminokyselin; potkani Long-Evans; dizocilpinmaleát; Rats; Locomotion; Memory; Animals; Spatial Behavior; mužské pohlaví; Disease Models, Animal; modely nemocí na zvířatech